The lawman returns eaudiobook - Eason, Lynette (Wrangler's Corner, 2019)
A dangerous homecoming for a deputy in this classic romantic suspense novel by bestselling author Lynette Eason Deputy Clay Starke has come home to Wrangler's Corner for one reason only: to solve his brother's murder. Denied the official resources that will help him unravel the case, Clay is forced to rely on his wits—and on the help of beautiful social worker Sabrina Mayfield. But Sabrina's willingness to assist him soon draws her into the troubles of Clay's past. Now both Clay and Sabrina have targets on their backs, and Clay is at risk of losing not only his heart, but also his life. Will finding his brother's killer cost him the woman he has come to love?